Association Between IL7R Promoter Polymorphisms and Multiple Sclerosis in Turkish Population - ARMAN, AHMET (HUMANA PRESS INC, 2019)
Multiple sclerosis (MS) is a chronic progressive neurodegenerative disease that affects myelin fibers within the central nervous system resulting in neurological impairment. Although the etiology of MS is not fully understood, environmental and genetic factors are thought to play important roles. IL7R gene polymorphisms which are associated with several autoimmune diseases have also been implicated as a genetic factor for MS following genome-wide association studies. To further examine this association, we investigated the association between MS and IL7R gene -449 (A/G), -504 (T/C), and -1085 (G/T) promoter polymorphisms in Turkish population. Three hundred sixty-four MS patients and 191 healthy controls were involved in this study. Three polymorphic regions in the promoter of IL7R were identified and these regions were amplified by appropriate primers. The PCR products were digested by PstI enzyme for -504 (T/C) SNP and HphI enzyme for -1085 (G/T) and -449 (A/G) SNPs and genotyping was done based on digested PCR product sizes. Genotype distributions and allele frequencies of -449 polymorphism did not show any significant association with MS directly (p=0.120 and p=0.490, respectively). But the genotypes of IL7R -449 GA for AOMS and AA for EOMS were a risk factor in according to age of onset (p=0.002, OR=4.021, 95% CI=1.642-9.845). Furthermore, IL7R -449 A allele was found to be a risk factor for EOMS (p=0.011, OR=1.3, 95% CI=1.107-1.527). Significant association was seen between IL7R -504 TC heterozygote genotype and MS (p=0.02, OR=1.702, 95% CI=1.169-2.478). The IL7R -1085 (G/T) polymorphism did not show association with MS; however, the haplotype of ACG may be susceptibility to MS and RRMS (p=0.035, OR=1.349, 95% CI=1.020-1.785, and p=0.041, OR=1.368, 95% CI=1.012-1.850, respectively) and the haplotypes of ACG, ATT, and GTG demonstrate a protective effect in EOMS (p=0.008, OR=0.326, 95% CI=0.136-0.782, p=0.012 and p=0.012, OR=0.462, 95% CI=0.249-0.859, respectively). RRMS frequency in the Turkish population was decreased and SPMS frequency was strongly increased based on comparison to results from other populations. Furthermore, male patients had an increased frequency of SPMS significantly (p=0.033, OR=1.667, 95% CI=1.036-2.682). In conclusion, this is the first study to show a significant association between the IL7R promoter polymorphisms and the age of onset of MS.
Keywords: IL7R; Polymorphism; Multiple sclerosis; Inflammation; RECEPTOR-ALPHA GENE; GENOME-WIDE ASSOCIATION; CD4 T-CELLS; INTERLEUKIN-7 RECEPTOR; IL-7; EXPRESSION; RISK; SUSCEPTIBILITY; PROLIFERATION; GUIDELINES